Chitosan: A promising plant stimulant - Walled Fouad Abobatta (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2023)
Chitosan is a natural polymer produced from the cell walls of fungi and the exoskeleton of crustaceans. Chitosan has exceptional qualities, such as non-toxicity, biodegradability, biocompatibility, affordability, and its capacity to function as a proteinase inhibitor by way of the formation of phytoalexin. Furthermore, positive ionic charges on the chitosan molecule increase plant immunity and defense systems against pathogens, promote plant growth, and increase yield. Chitosan plays a significant role, particularly in reducing adverse effects of abiotic stress like salinity and drought, by affecting the formation of Reactive Oxygen Species (ROS) such as proline, antioxidant enzyme activities, and total soluble sugars, which reverse the adverse effects of stress, improve the initiation of the antioxidant system, and increase photosynthesis, consequently improving plant growth and yield. Furthermore, chitosan treatment could suppress virus infections regardless of virus types as well as plant species. There are numerous physiological responses to chitosan application to improve plant immunity and defense systems, such as the synthesis of antioxidant enzymes to enhance plant resistance against pathogens, particularly fungi and bacterial infections. There are numerous benefits to chitosan, including inducing defense genes in numerous species, improving salt tolerance, enhancing plant growth under abiotic stress, improving germination parameters, increasing seedlings' survival, and consequently, improving plant resistance to pathogen infection, increasing tolerance to abiotic stress, and improving plant growth and productivity. Furthermore, it extends the shelf life and improves the fruit quality of numerous fruits when used as a coating film.